Economic and water dependence among regions: The case of Alto Tiete, Sao Paulo State, Brazil - Keyi Ando Ussami; Joaquim José Martins Guilhoto (EconomiA, 2018)
To illustrate the importance of the regional scale of water uses, this paper identifies the direct and indirect water use of the Sao Paulo State Water Resources Management Units (WRMUs) and the rest of Brazil by focusing on Alto Tiete WRMU. The Alto Tiete WRMU has been suffering from water scarcity and its boundaries are similar to that of the Sao Paulo Metropolitan Region. To this aim, a subnational interregional input-output model was estimated with a high degree of disaggregation (83 sectors and 23 regions) and a detailed estimation of water use coefficients that differ not only among sectors but also among the regions was applied. These coefficients also took into account their regions' endoclimatic characteristics. The resulting database allows quantifying the water embedded in the goods (virtual water) traded among Alto Tiete WRMU and other regions. The results show that despite its commercial trade surplus, Alto Tiete actually presents a virtual water trade deficit, showing that it exports goods that are less intensive in water use, while importing goods that are more water intensive. This study provides new insights and a scientific reference for public policies concerned with the management of water resources at the regional scale.
Keywords: 330; Brazil; Interregional input-output model; Virtual water; Water footprint